Lead ion sensor based on composite liquid gate transistor as well as preparation method and application of lead ion sensor
By using nitrogen-doped graphene/gold nanoparticle composite material and glutathione molecular probe in a composite liquid gate transistor, the problems of slow response speed and narrow linear range of existing lead ion detection methods have been solved, achieving high sensitivity and rapid lead ion detection.
Patent Information
- Application Number
- CN202411769018.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-02-28
AI Technical Summary
Existing lead ion detection methods suffer from slow response speed, narrow linear range, high difficulty in two-dimensional material deposition process, and low reusability of precious metal electrodes.
A lead-ion sensor based on a composite liquid gate transistor is designed. A nitrogen-doped graphene/gold nanoparticle composite material is used as the substrate, combined with a glutathione molecular probe, to achieve full collection and amplification of electrical signals by modifying the gate surface.
It achieves highly sensitive detection of lead ions, with a detection limit of 10-11 M and a response time as low as 100 s, exhibiting high selectivity and specificity.
Smart Images

Figure CN119534588A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of biosensors, and in particular to a lead ion sensor based on a composite liquid-gate transistor and a preparation method and application thereof. Background Art
[0002] Lead is widely used in industrial and daily industries such as solar cells, batteries, radiation protection, cable sheaths and machinery manufacturing due to its unique physical and chemical properties. However, the leaked lead ions are extremely toxic to the organisms and the environment, and can easily cause irreversible effects on the environment and life and health. Therefore, it is of great significance to monitor the changes of lead ions in the environment in a timely and accurate manner.
[0003] Traditional laboratory detection methods such as atomic absorption, emission spectroscopy and plasma mass spectrometry have high accuracy and sensitivity for lead ions, but they also have some limitations: (1) the sample requires complex and time-consuming pretreatment; (2) the equipment and consumables are expensive; (3) the equipment accessories are large and bulky, which is not conducive to carrying and rapid on-site detection. Therefore, the development of a rapid, highly sensitive, highly selective and low-cost lead ion detection method is of great significance to environmental protection and medical fields.
[0004] Field effect transistor lead ion sensors identify target ions based on changes in electrochemical signals caused by the interaction between ions and functionalized gates. They have the advantages of good selectivity, high sensitivity, fast response, and economic portability. People often deposit or transfer two-dimensional materials between the source and drain as the conductive channel of transistor sensors, capture target ions by modifying probe molecules, and adjust the gate voltage to achieve electrical signal changes. The deposition process of these two-dimensional materials is difficult, and the electrochemical reaction can easily cause the recognition probe to fall off and fail, and the reuse rate of precious metal electrodes is low. In addition, the electrical amplification characteristics of transistors are not fully utilized.
[0005] Therefore, the technical problems that need to be solved at present are to design a composite gate that is easy to modify two-dimensional materials and precious metal nanoparticles, to construct a new liquid gate field effect transistor lead ion sensor, and to realize the full collection and amplification of the identification electrical signals between the gate and the source and drain. Summary of the invention
[0006] The purpose of the present invention is to provide a lead ion sensor based on a composite liquid gate transistor and a preparation method and application thereof, so as to solve the technical problems of slow lead ion detection response speed and narrow linear range in the prior art.
[0007] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0008] The present invention provides a lead ion sensor based on a composite liquid gate transistor, comprising a substrate and a source electrode and a drain electrode arranged on the substrate; and a composite gate;
[0009] A graphene channel is formed between the source electrode, the drain electrode and the substrate;
[0010] The composite gate is a base gate on which a nitrogen-doped graphene / gold nanoparticle composite material is fixed as a substrate, and a molecular probe is fixed on the substrate.
[0011] Furthermore, the base gate is an Ag / AgCl electrode or a glassy carbon electrode.
[0012] Furthermore, a single layer of graphene is provided on the surface of the graphene channel;
[0013] The width of the graphene channel is 0.2-0.3 mm, and the length of the graphene channel is 4-8 mm.
[0014] Furthermore, the molecular probe is a glutathione molecular probe, and the glutathione molecular probe is fixed on the nitrogen-doped graphene / gold nanoparticle composite material via a thiol group.
[0015] Furthermore, the source electrode and the drain electrode are both formed by sequentially compounding a metal layer, a transition layer and a substrate, the metal layer is a gold layer, and the transition layer is a chromium layer.
[0016] Furthermore, the thickness of the chromium layer is independently 6 to 12 nm, and the thickness of the gold layer is independently 40 to 90 nm.
[0017] The present invention also provides a method for preparing a lead ion sensor based on a composite liquid gate transistor, comprising the following steps:
[0018] (1) preparing a source electrode and a drain electrode on the surface of a substrate so that a channel exists between the source electrode and the drain electrode;
[0019] (2) Laying graphene on the channel surface between the source and drain electrodes, and polishing the glassy carbon electrode to make it smooth as a gate, thereby obtaining a graphene transistor;
[0020] (3) fixing the nitrogen-doped graphene / gold nanoparticle composite material as a substrate on the surface of the base gate of the graphene transistor;
[0021] (4) Fixing the glutathione molecular probe on the surface of the substrate obtained in step (3) to obtain a transistor lead ion sensor.
[0022] Furthermore, the preparation of the source electrode and the drain electrode comprises the following steps: a chromium layer and a gold layer are sequentially deposited on the surface of the substrate by a thermal evaporation coating method.
[0023] The present invention also provides an application of a lead ion sensor based on a composite liquid-gate transistor in lead ion detection.
[0024] Beneficial effects of the present invention:
[0025] The lead ion sensor based on the composite liquid gate transistor of the present invention fixes the base nitrogen-doped graphene / gold nanoparticles on the surface of the base gate to form a composite gate; and modifies glutathione molecules on the substrate. The probe is fixed on the composite gate surface of the field effect transistor, and glutathione can complex with the lead ions in the solution, thereby changing the double electric layer interface characteristics between the transistor and the sample solution, causing the current in the graphene channel to change, and the gate voltage is used to regulate and amplify the channel current to achieve high-sensitivity detection of trace lead ions; the transistor lead ion sensor provided by the present invention fixes the drain voltage and changes the gate voltage, and the minimum detection limit of lead ions can reach 10 -11 M, the minimum response time is 100s. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 Schematic diagram of the source-drain structure of a lead ion sensor based on a composite liquid-gate transistor in an embodiment of the present invention;
[0027] Figure 2 This is a diagram of the step-by-step modification of the gate of the lead ion sensor based on the composite liquid gate transistor in an embodiment of the present invention;
[0028] Figures 3-4 Schematic diagram of the change of the double electric layer when detecting lead ions in Example 3;
[0029] Figure 5 The transfer characteristic curve of the lead ion sensor based on the composite liquid gate transistor prepared in Examples 1 and 2 of the present invention when detecting lead ions;
[0030] Figure 6 The current-time curve of the lead ion sensor based on the composite liquid gate transistor prepared in Examples 1 and 2 of the present invention when detecting lead ions;
[0031] Figure 7 The lead ion sensor based on the composite liquid gate transistor prepared in Examples 1 and 2 of the present invention detects a concentration of 10 -6 Current-time curve for M lead ions;
[0032] Figure 8 The linear relationship diagram of the potential shift of the Dirac point and the logarithm of the lead ion concentration;
[0033] Fig. 9 This is a schematic diagram of the principle of detecting lead ions using a field effect transistor ion sensor with a functionalized graphene-modified gate in an embodiment of the present invention. DETAILED DESCRIPTION
[0034] The present invention provides a lead ion sensor based on a composite liquid gate transistor, comprising a substrate and a source electrode and a drain electrode arranged on the substrate; and a composite gate;
[0035] A graphene channel is formed between the source electrode, the drain electrode and the substrate;
[0036] The composite gate is a base gate on which a nitrogen-doped graphene / gold nanoparticle composite material is fixed as a substrate, and a molecular probe is fixed on the substrate.
[0037] In the present invention, the base gate is an Ag / AgCl electrode or a glassy carbon electrode, preferably a glassy carbon electrode.
[0038] In the present invention, there is no particular limitation on the type and source of the substrate. Any sensor substrate well known to those skilled in the art may be used, preferably electronic grade glass.
[0039] In the present invention, there is no special limitation on the size of the substrate, which can be adjusted according to the size of the device. In the present invention, the length and width of the substrate are preferably 10-15 mm independently, more preferably 12 mm; the thickness of the substrate is preferably 2 mm.
[0040] In the present invention, a single layer of graphene is provided on the surface of the graphene channel;
[0041] The width of the graphene channel is 0.2-0.3 mm, preferably 0.25 mm; the length of the graphene channel is 4-8 mm, preferably 6-8 mm.
[0042] In the present invention, the graphene preferably fills the gap between the source and the drain. In the present invention, the graphene channel is preferably a single layer of graphene. In the present invention, the graphene channel can increase the sensitivity of the sensor.
[0043] In the present invention, the source and drain are preferably arranged in sequence and at intervals on the same surface of the substrate; the present invention has no special requirements on the specific positions of the source and drain, and they can be arranged according to positions familiar to those skilled in the art.
[0044] In the present invention, the molecular probe is a glutathione molecular probe, and the glutathione molecular probe is fixed on the nitrogen-doped graphene / gold nanoparticle composite material via a thiol group.
[0045] In the present invention, the source electrode and the drain electrode are both formed by sequentially compounding a metal layer, a transition layer and a substrate, the metal layer is a gold layer, and the transition layer is a chromium layer.
[0046] In the present invention, the thickness of the chromium layer is independently 6 to 12 nm, preferably 7 to 11 nm, and more preferably 8 to 10 nm; the thickness of the gold layer is independently 40 to 90 nm, preferably 50 to 80 nm, and more preferably 60 to 70 nm.
[0047] In the present invention, the chromium layer enables the gold layer to be firmly attached to the substrate surface, thereby preventing the gold layer from falling off during subsequent operations.
[0048] In the present invention, there is no special limitation on the shapes of the source and drain, and the shapes can be designed using positions familiar to those skilled in the art.
[0049] The present invention utilizes graphene with high specific surface area and conductivity as a modified material matrix, further broadens the performance of the composite material by introducing metal nanoparticles, and provides a probe substrate at the same time.
[0050] In the present invention, the concentration of the composite material for modifying the gate surface is preferably 2 mg / mL.
[0051] In the present invention, the concentration of the glutathione molecular probe is 25 to 35 mM, preferably 30 mM.
[0052] The present invention also provides a method for preparing a lead ion sensor based on a composite liquid gate transistor, comprising the following steps:
[0053] (1) preparing a source electrode and a drain electrode on the surface of a substrate so that a channel exists between the source electrode and the drain electrode;
[0054] (2) Laying graphene on the channel surface between the source and drain electrodes, and polishing the glassy carbon electrode to make it smooth as a gate, thereby obtaining a graphene transistor;
[0055] (3) fixing the nitrogen-doped graphene / gold nanoparticle composite material as a substrate on the surface of the base gate of the graphene transistor;
[0056] (4) Fixing the glutathione molecular probe on the surface of the substrate obtained in step (3) to obtain a transistor lead ion sensor.
[0057] In the present invention, the preparation of the source electrode and the drain electrode comprises the following steps: a chromium layer and a gold layer are sequentially deposited on the surface of the substrate by a thermal evaporation coating method.
[0058] The present invention also provides an application of a lead ion sensor based on a composite liquid-gate transistor in lead ion detection.
[0059] In the present invention, the principle of lead ion detection is that the lead ions are captured by molecular probes modified on the gate substrate nitrogen-doped graphene / gold nanoparticle composite material, and then the Dirac point of the device changes to achieve sensing.
[0060] The detection mechanism of the transistor lead ion sensor provided by the present invention is as follows Figures 3-4As shown, the gate electrode and the graphene channel are connected by electrolyte to form a "double capacitor" structure, and the voltage applied between the gate and the graphene channel is constant. The voltage applied to the gate changes the double-layer interface characteristics when the fixed glutathione and lead ions are complexed, and at the same time causes the current in the graphene channel to change. By detecting the current change in the channel, the trace lead ions in the solution can be quantitatively detected.
[0061] The present invention preferably cleans and dries the substrate before use. In the present invention, the cleaning is preferably ultrasonic cleaning, and more preferably acetone, isopropanol and ethanol are used for ultrasonic cleaning in sequence. In the present invention, the ultrasonic cleaning time of acetone, isopropanol and ethanol is independently preferably 10 to 30 minutes, more preferably 20 minutes. The present invention has no particular limitation on the frequency of the ultrasonic cleaning, and the frequency familiar to those skilled in the art can be used. In the present invention, the drying is preferably oven drying.
[0062] In the present invention, after the source and drain are prepared, the present invention lays graphene on the channel between the source and the drain to obtain a graphene transistor. In the present invention, the laying of the graphene preferably includes: transferring a metal substrate single-layer graphene to the channel between the source and the drain by wet transfer. In the present invention, the metal substrate single-layer graphene is preferably a copper substrate CVD method single-layer graphene. The present invention has no special limitation on the source of the metal substrate single-layer graphene, and a commercial product well known to those skilled in the art can be used, or it can be prepared according to a preparation method well known to those skilled in the art. The present invention preferably removes excess graphene on both sides of the channel after the transfer. The present invention has no special requirements for the method of removing excess graphene. In a specific embodiment of the present invention, it is preferred to use tweezers to remove excess graphene.
[0063] The present invention has no special limitation on the operation of the wet transfer, and the technical solution of wet transfer of single-layer graphene well known to those skilled in the art can be adopted.
[0064] After the transfer of graphene is completed, the present invention preferably anneals the transferred product to obtain a graphene crystal tube. In the present invention, the annealing temperature is preferably 100-130°C, more preferably 110°C: the annealing time is preferably 20-30 minutes, more preferably 25 minutes. In the present invention, the annealing can remove moisture from the sample surface and make the graphene more closely bonded to the substrate.
[0065] The present invention uses a glassy carbon electrode (GCE) as the gate. A glassy carbon electrode with a diameter of 3 mm is placed on the suede and then coated with 1.0 μm, 0.3 μm, and 0.05 μm Al 2 O 3 The powder was polished to a mirror finish and then treated with 1:1 HNO 3, acetone, anhydrous ethanol, and double distilled water for 5 minutes, and then N 2 Blow dry and place the clean bare electrode in 0.1mmol / LK 3 [Fe(CN) 6 ] and 0.2mol / L KCl mixed solution, and electrochemical treatment was carried out in the voltage range of -0.6 to +0.2V until a stable current response was obtained. A complete transistor gate was obtained, and the graphene transistor was prepared.
[0066] After obtaining the graphene transistor, the present invention preferably fixes the base nitrogen-doped graphene / gold nanoparticle composite material on the surface of the transistor gate to provide a site for probe modification.
[0067] In some embodiments, the preparation method of gold nanoparticles in the substrate material is as follows: 98 mL of distilled water is measured with a measuring cylinder into a 200 mL double-necked flask, and 2 mL of 50 mmol·L -1 Place the tetrachloroauric acid solution on a magnetic stirrer and stir until it is evenly dispersed. Connect the condenser and heat to 100°C. When reflux begins, quickly add 10mL of 38.8mmoL·L -1 Sodium citrate solution, under continuous stirring, the solution slowly changes from light yellow to wine red, and continues to stir and reflux for 20 minutes. After cooling to room temperature, store in the refrigerator for later use.
[0068] In some embodiments, the preparation method of nitrogen-doped graphene / gold nanoparticle composite material is: synthesized by hydrothermal reduction method using urea as a reducing agent and nitrogen source: weigh 20 mg of graphene oxide and add 20 mL of distilled water into a 50 mL flask, ultrasonicate for 1 h to form a uniform dispersion, add ammonia water to adjust the pH value of the solution to 10.0, then add 1.2 g of urea and 4 mL of the AuNPs sol prepared above, place the flask on a magnetic stirrer, and reflux at 100 ° C for 24 h under nitrogen protection. Repeatedly centrifuge and wash with distilled water until the washing solution is neutral, and the obtained black solid is vacuum dried at 60 ° C to obtain the AuNPs / NG composite material.
[0069] After obtaining a graphene transistor with a gate modified fixed substrate, the present invention preferably fixes glutathione molecules on the surface of the substrate to obtain a lead ion sensor based on a functionalized graphene field effect transistor. In the present invention, the preferred glutathione molecules are fixed to the surface of the substrate via thiol modification. The present invention has no particular limitation on the operation of fixing the glutathione molecules, and a fixation method familiar to those skilled in the art can be used.
[0070] The present invention also provides the use of the transistor-based lead ion sensor described in the above technical solution or the transistor lead ion sensor prepared according to the above technical solution in lead ion detection, wherein the gate and graphene channel of the graphene transistor-based ion sensor are partially immersed in an electrolyte containing the ions to be detected. In the present invention, the electrolyte is preferably 1x PBS: the pH value of the electrolyte is preferably 7 to 7.5. In the present invention, the gate and the graphene channel are connected through the electrolyte, and the voltage input to the gate is used to control the current of the graphene channel.
[0071] When using the transistor lead ion sensor provided by the present invention to perform quantitative determination of lead ions, it is preferred to prepare a standard solution containing lead ions, determine a standard curve of the Dirac point change and the lead ion concentration, and determine the concentration of the lead ions to be measured based on the standard curve and the Dirac point change obtained in the test.
[0072] The transistor lead ion sensor provided by the present invention can detect the ion concentration by directly immersing it in the solution to be tested. It is a label-free detection method. It can detect samples with high sensitivity and has good stability. The three-electrode structure and graphene channel of the transistor lead ion sensor provided by the present invention make it very sensitive to voltage changes. A small voltage change will cause a corresponding current change. It has high sensitivity. The graphene transistor lead ion sensor provided by the present invention can detect ion concentrations as low as 10 -11 Detection of extremely trace lead ions in M.
[0073] Table 1 Comparison of methods reported in recent years for detecting lead ions using field effect transistors
[0074]
[0075]
[0076] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0077] Example 1
[0078] Thermal evaporation coating:
[0079] Cut the electronic grade glass into 12×12m size, clean it with acetone, isopropanol, ethanol and water ultrasonically for 20 minutes, dry it in a drying oven, and then stick the glass piece on a mask of a specific shape with high temperature glue. Weigh appropriate amount of chromium and gold and put them into a tungsten boat to prepare for vacuum thermal evaporation coating.
[0080] When evaporating, chromium is evaporated first: the thickness is 8nm.
[0081] Then evaporate the gold layer: the thickness is 80nm.
[0082] The obtained electrode shape, structure and size are as follows Figure 1 shown. Figure 1 In the figure, S is the source, D is the drain, and the 0.25 mm wide channel between the source and the drain becomes the graphene channel after the graphene is transferred.
[0083] Wet transfer graphene:
[0084] Cut the purchased graphene into the required size, and then put PMMA / graphene / Cu into the H 2 O, HCl and CuSO 4 ﹒ 5H 2 O (50mL:50mL:10g). After 30min, the copper substrate was etched clean and turned into transparent PMMA / graphene.
[0085] Use a glass slide to transfer PMMA / graphene to ultrapure water and wash it three times to clean the etching solution. Transfer the washed PMMA / graphene to the clean electrode and lay it flat on the channel between the source and drain on the surface of the electrode sheet. Dry it naturally until no surface moisture is observed with the naked eye, then place it on a hot plate for annealing at 110°C to completely remove the moisture on the sample surface to obtain a PMMA / graphene / electrode sheet.
[0086] After cooling to room temperature, use tweezers to remove the excess PMMA / graphene on both sides of the channel. Finally, immerse the device with transferred graphene in acetone solution for 3min, 5min, and 10min to remove the PMMA layer. After immersion, rinse the device with ethanol and place it on a heating table at 95℃ for 10min to remove the surface PMMA. After 3h, wash the graphene transistor with deionized water and dry it naturally. The graphene channel is prepared and stored in a clean watch glass.
[0087] Example 2
[0088] Preparation of the gate:
[0089] A glassy carbon electrode with a diameter of 3 mm was placed on the suede and coated with 1.0 μm, 0.3 μm, and 0.05 μm Al 2 O 3 The powder was polished to a mirror finish and then treated with 1:1 HNO 3 , acetone, anhydrous ethanol, and double distilled water for 5 minutes, and then N 2 Blow dry and place the clean bare electrode in 0.1mmol / LK 3 [Fe(CN) 6] and 0.2 mol / L KCl mixed solution, and electrochemical treatment was performed in the voltage range of -0.6 to +0.2 V until a stable current response was obtained. The gate preparation was completed.
[0090] Gate modification:
[0091] Preparation of gold nanoparticles: Use a measuring cylinder to measure 98 mL of distilled water into a 200 mL double-necked flask, add 2 mL of 50 mmol·L -1 Place the tetrachloroauric acid solution on a magnetic stirrer and stir until it is evenly dispersed. Connect the condenser and heat to 100°C. When reflux begins, quickly add 10mL of 38.8mmoL·L -1 Sodium citrate solution, under continuous stirring, the solution slowly changes from light yellow to wine red, and continues to stir and reflux for 20 minutes. After cooling to room temperature, store in the refrigerator for later use.
[0092] The preparation method of nitrogen-doped graphene / gold nanoparticles is as follows: urea is used as a reducing agent and a nitrogen source for synthesis by hydrothermal reduction. 20 mg of graphene oxide is weighed and added to 20 mL of distilled water in a 50 mL flask, and ultrasonicated for 1 h to form a uniform dispersion. Ammonia water is added to adjust the pH value of the solution to 10.0, and then 1.2 g of urea and 4 mL of the AuNPs sol prepared above are added. The flask is placed on a magnetic stirrer and refluxed at 100 ° C for 24 h under nitrogen protection. The washing solution is repeatedly centrifuged with distilled water until the washing solution is neutral, and the obtained black solid is vacuum dried at 60 ° C to obtain the AuNPs / NG composite material.
[0093] The nitrogen-doped graphene / gold nanoparticle composite material prepared above was dispersed in a 1% (v / v) acetic acid solution containing 1% (w / v) chitosan to prepare a 2 mg mL -1 Use a 10 μL microinjector to take a certain amount of dispersion droplets and apply them on the polished and smooth surface of the glassy carbon electrode, and let it dry naturally.
[0094] Fixing glutathione molecular probe: drop 10 μL of 30 mM glutathione solution onto the surface of the gate, and wash three times with PBS buffer after 5 hours: wash away the unfixed glutathione molecular probe and other impurities on the gate, and the source and drain prepared in Example 1 and the gate prepared in Example 2 form a transistor lead ion sensor.
[0095] Example 3
[0096] This embodiment provides a method for detecting lead ion concentration, comprising the following steps:
[0097] The lead ion concentration was tested using the transistor lead ion sensor prepared in Examples 1 and 2. Its source, drain and gate electrodes were connected to two combined Keithley data source meters (Keithley 2400). The gate voltage Vc and the source-drain voltage V DS It is controlled by a Labview program in the computer.
[0098] The modified gate electrode was thoroughly cleaned with PBS solution to remove the residue left on the electrode. The test was performed in a container filled with 4mL of PBS solution. During the test, a lead ion solution of a specific concentration was added to the PBS solution to obtain different lead ion concentrations. The device was placed in PBS buffer and 10μL of the prepared lead ion solution was added to the PBS buffer solution in sequence according to the concentration gradient for subsequent testing.
[0099] Transfer characteristic curve test:
[0100] The source-drain voltage is set to a constant value (V DS =0.05V), the channel current I between the source and drain is measured when the gate voltage changes continuously from 0V to 1V DS Then the concentration of lead ions in the solution is changed and measured in sequence, and the voltage value change of the Dirac point before and after is calculated; the transfer characteristic curve obtained is as follows Figure 5 As shown in Figure 2, the change in the interface will change the potential on the device surface, thus causing the characteristic curve to move. Figure 5 It can be seen that as the lead ion concentration increases, the current changes.
[0101] Standard curve drawing: The source-drain voltage is set to a constant value (V DS =0.05V), the gate voltage was changed continuously from 0V to 1V, and lead ion solutions of different concentrations were prepared according to the method in Example 3, and the lead ion concentration was 10 -10 M, 10 -9 M, 10 -8 M, 10 -7 M, 10 -6 M, 10 -5 M, 10 -4 The Dirac point change value of the transistor lead ion sensor at 2000 ℃ was measured. The test was repeated 3 to 5 times, and the average value was taken. A curve was drawn with the lead ion concentration as the horizontal axis and the Dirac point change value as the vertical axis. It can be seen from the curve that the Dirac point change value and the lead ion concentration have a good linear relationship, and the R of the fitting line is 2 The value is 0.99875, such as Figure 8 As shown, when detecting the concentration of lead ions to be measured, the concentration of lead ions can be obtained according to the change value of the transistor Dirac point and the standard curve.
[0102] It can be seen from the above embodiments that the present invention provides a lead ion sensor based on a composite liquid gate transistor and its preparation method and application. The present invention uses a glassy carbon electrode as a gate and modifies a layer of nitrogen-doped graphene on its surface as a substrate to introduce gold nanoparticles to broaden its conductive properties in preparation for subsequent comparisons. At the same time, the probe glutathione is modified to the surface of the substrate material, which can complex with the lead ions in the solution, thereby changing the double layer characteristics between the transistor and the sample solution, and achieving the purpose of quantitative analysis by measuring the change in the Dirac point of the device. The lead ion concentration detection method of the present invention can achieve a minimum detection limit of 10 as the concentration of the target changes. -11 M, the response time is as low as 100s, and the sensor has high selectivity and specificity.
[0103] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A lead ion sensor based on a composite liquid gate transistor, characterized in that: It includes a substrate, a source electrode and a drain electrode disposed on the substrate; and a composite gate; A graphene channel is formed between the source electrode, the drain electrode and the substrate; The composite gate is a base gate on which a nitrogen-doped graphene / gold nanoparticle composite material is fixed as a substrate, and a molecular probe is fixed on the substrate.
2. The lead ion sensor based on the composite liquid gate transistor according to claim 1, characterized in that: The base grid is an Ag / AgCl electrode or a glassy carbon electrode.
3. The lead ion sensor based on the composite liquid gate transistor according to claim 1 or 2, characterized in that: A single layer of graphene is provided on the surface of the graphene channel; The width of the graphene channel is 0.2-0.3 mm, and the length of the graphene channel is 4-8 mm.
4. The lead ion sensor based on the composite liquid gate transistor according to claim 3, characterized in that: The molecular probe is a glutathione molecular probe, and the glutathione molecular probe is fixed on the nitrogen-doped graphene / gold nanoparticle composite material via a thiol group.
5. The lead ion sensor based on the composite liquid gate transistor according to claim 1, 2 or 4, characterized in that: The source electrode and the drain electrode are both formed by sequentially compounding a metal layer, a transition layer and a substrate, the metal layer is a gold layer, and the transition layer is a chromium layer.
6. The lead ion sensor based on the composite liquid gate transistor according to claim 5, characterized in that: The thickness of the chromium layer is independently 6 to 12 nm, and the thickness of the gold layer is independently 40 to 90 nm.
7. The method for preparing a lead ion sensor based on a composite liquid gate transistor according to any one of claims 1 to 6, characterized in that: The following steps are involved: (1) preparing a source electrode and a drain electrode on the surface of a substrate so that a channel exists between the source electrode and the drain electrode; (2) Laying graphene on the channel surface between the source and drain electrodes, and polishing the glassy carbon electrode to make it smooth as a gate, thereby obtaining a graphene transistor; (3) fixing the nitrogen-doped graphene / gold nanoparticle composite material as a substrate on the surface of the base gate of the graphene transistor; (4) Fixing the glutathione molecular probe on the surface of the substrate obtained in step (3) to obtain a transistor lead ion sensor.
8. The preparation method according to claim 7, characterized in that: The preparation of the source electrode and the drain electrode comprises the following steps: a chromium layer and a gold layer are sequentially deposited on the surface of the substrate by a thermal evaporation coating method.
9. Application of the lead ion sensor based on the composite liquid gate transistor according to any one of claims 1 to 6 in lead ion detection.
Citation Information
Patent Citations
Real-time detection of water contaminants
CN107076698A
Detection method and sensor for detecting L-cystine based on glutathione composite film grid gold electrode
CN108802124A
Biosensor for detecting lead and preparation method and application thereof
CN110579523A
Graphene transistor copper ion sensor and preparation method and application thereof
CN111220669A
Pulse-driven capacitive detection for field-effect transistors
CN111771122A